Efficacy of Hiporhamin (Erebra) in the Treatment and Prevention of Viral Diseases in Children - I.B. Yershova (Zaslavsky O.Yu., 2014)
The article presents the results of both experimental and clinical studies of Erebra, active substance of which is hiporhamin - dry purified extract from the leaves of sea buckthorn. The effectiveness of the drug has been shown in children with various viral infections.